Contribuições da Teoria Histórico-Cultural e da Atividade no ensino-aprendizagem de Geografia : a compreensão do conceito de bioma Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This thesis presents the results of the doctoral research entitled “Contributions of Historical-Cultural Theory and Activity in the teaching-learning of Geography: understanding of the concept of the Amazon biome” developed at a private school in Manaus/AM, with the participation of 38 7th grade students. Such experience is part of the research line ‘Training and Praxis of the Educator in the Face of Amazonian Challenges’, of the Graduate Program in Education at the Federal University of Amazonas (PPGE / UFAM), and it aimed to understand how the assumptions of Historical-Cultural Theory and Activity that guide pedagogical practices that promote autonomy, can contribute to the construction of geographical concepts, instructing 7th grade students in understanding of reality. To do so, we started with a bibliographic review on the themes of Historical-Cultural Theory and Activity Theory, allied to School Geography, seeking to articulate them, in order to, through the reading and interpretation of concrete reality, provide a methodological path of teaching-learning capable of instructing teachers and students in the construction of contextual, real and autonomous knowledge. In order to carry out an interlocution between Geographic Education and Historical-cultural and Activity Theory, we seek, with this research, to answer the following problem: how the assumptions of Historical-Cultural Theory and Activity, guiding pedagogical practices that promote of autonomy, can they contribute to the construction of geographical concepts, instrumentalizing 7th grade students in understanding reality? In our work, we list the following specific objectives: a) discuss, based on the assumptions of Historical-Cultural Theory and Activity, the objective and subjective elements that motivate learning; b) know the students' perception and level of interaction in relation to the concepts and elements that make up the Amazonian context; c) to identify how the activities of study and research in Geography classes contribute to the generation of needs and the appropriation of concepts related to the Amazonian reality. Based on this, we seek to discuss, based on the assumptions of Historical-Cultural Theory and Activity, the objective and subjective elements that motivate learning, which also served as self-knowledge, since all human beings are in this process, regardless of age or of the cognitive stage in which they are. To this end, the production of data took place through the teaching of Geography classes on the themes of the North and Amazon Region, in addition to pedagogical activities such as the development of a research project, the construction of mental maps, and the questionnaires. The results show that the assumptions of Historical-Cultural Theory and Activity, combined with pedagogical practices, contribute to the appropriation of geographic concepts by students, in the understanding of concrete reality and in the resignification of teaching work.
Keywords: Geografia - Estudo e ensino; Geografia (Ensino fundamental); Biomas - Amazônia; CIÊNCIAS HUMANAS: EDUCAÇÃO; Teoria Histórico-Cultural; Teoria da Atividade; Ensino de Geografia; Bioma Amazônia; Ensino Fundamental